EIB Working Paper 2022/15 - Estimating financial integration in Europe How to separate structural trends from cyclical fluctuations - European Investment Bank (European Investment Bank, 2022)
"Financial integration, broadly defined as the intensity of cross-border linkages between financial markets, has the potential to channel capital to where it is most productive, bringing many benefits. However, some financial integration is cyclical, increasing economic upswings and declining during down-turns. Of more long-term benefit is financial integration driven by structural factors such as the reductions in exchange rate risk and the increased regulatory or supervisory convergence associated with the establishment of a currency union, such as Europe's Economic and Monetary Union. This paper presents a new indicator of de facto financial integration in the European Union. Analysing this indicator alongside different financial and macroeconomic variables makes it possible to separate the impact of cyclical boom-bust shocks from the influence structural factors. It shows that increasing structural financial integration tends to improve risk absorption and reduce income disparities among European countries. However, it also suggests that most of the movements in the indicator reflect business cycle dynamics, rather than structural integration. These results highlight the need to develop further policies to foster structural financial integration in the EU."